AKTIVITAS ANTIOKSIDAN DAN MUTU FISIK MASKER WAJAH BERBAHAN DAUN KELOR (Moringa Oleifera) DAN KOPI ROBUSTA(Coffea canephora var robusta) - Shiza Maunik Wijaya; Sri Wening (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The increase of air pollution in today’s environment is directly proportional to the increased in free radical compounds in the body, which can cause damage to the demis tissue and skin collagen, especially face. One of the effort that can be done to avoid this damage is by using natural face masks such as moringa leaves and robusta coffee. This study aims to analyze the content of antioxidant activity and the physical quality of face masks made from moringa leaves and robusta coffee. This research is an experimental research which is presented descriptively. This research consists of the process of making moringa leaf powder and robusta coffee, testing the antioxidant activity and physical quality of facial masks. Based on the results from the test of the content of antioxidant activity, it shows that the A3 formula has the highest value based on the test for the content of antioxidant activity, pH, drying time and organopeltic test as a whole with values of 75.28%, 6.0, 22.15 minutes and 3.6. In conclusion, moringa leaves and robustas coffee are recommended and can be used as a face mask formula with antioxidant activity and good physical quality for skin health.